2011
DOI: 10.1021/ac1030094
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characterization of Icosahedral Virus Ultra Structure, Stability, and Integrity Using Electrospray Differential Mobility Analysis

Abstract: We present a rapid and quantitative method to physically characterize the structure and stability of viruses. Electrospray differential mobility analysis (ES-DMA) is used to determine the size of capsomers (i.e., hexons) and complete capsids. We demonstrate how to convert the measured mobility size into the icosahedral dimensions of a virus, which for PR772 become 68.4 nm for vertex-to-vertex, 54.4 nm for facet-to-facet, and 58.2 nm for edge-to-edge lengths, in reasonable agreement with dimensions from transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…This size dependence is usually accounted for by calibrating CPCs against electrometers and is called the CPC collection efficiency (η CPC ) [30]. It should be pointed out that modifications, including use of different working fluids and operating temperatures can lower the size limit to ~ 1 nm [31]. Further discussion about the operating principle of the CPC can be found elsewhere [29].…”
Section: Condensation Particle Counter (Cpc)mentioning
confidence: 99%
“…This size dependence is usually accounted for by calibrating CPCs against electrometers and is called the CPC collection efficiency (η CPC ) [30]. It should be pointed out that modifications, including use of different working fluids and operating temperatures can lower the size limit to ~ 1 nm [31]. Further discussion about the operating principle of the CPC can be found elsewhere [29].…”
Section: Condensation Particle Counter (Cpc)mentioning
confidence: 99%
“…For example, a number of studies measured the size of both large and small viruses (Bacher et al, 2001;Bothner and Siuzdak, 2004;Wick et al, 2005;Hogan et al, 2006;Thomas et al, 2004;Cole et al, 2009;Kaddis et al, 2007;Laschober et al, 2008;Pease et al, 2009;Wick et al, 2007). Using ES-DMA size distributions Pease et al (2011) determined the symmetry and number of proteins per capsid for PR772 (Family Tectiviridae, Genus Tectivirus), a biosafety level 1 (BSL1) simulant of adenovirus. Lute et al (2008) and Wick et al (2007) extended ES-DMA analyses to viruses of particular interest to biomanufacturers and filter firms by characterizing the size distributions of murine minute virus (Family Parvoviridae, parvovirus) and the BSL1 models, PP7 (Family Leviviridae, Genus Levivirus) and X174 (Family Microvaridae, Genus Microvirus) (Wick et al, 2007) used in virus filtration studies (Lute et al, 2008) and in the Parenteral Drug Association's (PDA) new nomenclature standards for small and large virus retentive filters.…”
Section: Introductionmentioning
confidence: 99%
“…MS-based analysis of viral capsid assembly and stability is a good example of another interesting application. Pease et al, using ESI-DMA technique, have shown, in addition to previously described experiments (Bacher et al, 2001;Hogan et al, 2006), that it is possible to measure the geometry of the viral particles, their structure and integrity (Pease et al, 2011). As a model object, phage PR772 was used, which belongs to the Tectiviridae family.…”
Section: A Cdmsmentioning
confidence: 99%